Identifikasi Miskonsepsi Siswa pada Konsep Ikatan Kimia Menggunakan Tes Four-Tier Multiple-Choice (4TMC) - Islami, Dini; Suryaningsih, Siti; Bahriah, Evi Sapinatul (LPPM Universitas Negeri Jakarta, 2019)
Chemical Bonding is one of the chemicals with abstract concepts, and is admittedly difficult to understand and often leads to misconceptions in students. This study aims to identify student misconception on the concept of Chemical Bonding. The method used in this research is quantitative descriptive. The study was conducted on 31 January to 6 February 2018. The subjects of this study are X grade students academic year 2017/2018 with the number of samples of 48 students. The misconception identification was performed using a four-tier multiple-choice (4TMC) test instrument. Students' answers from the 4TMC test are then analyzed and categorized based on the students' level of understanding. The results showed that there was a misconception of 30.31% (low category). Significant misconceptions are identified as 8 out of 13 subconcepts of the Chemical Bonding they are Lewis Structure and the Octet Rule (33.33%), Metal Bond and Metal Properties (20.83%), Ionic Compounds and Covalent Compounds (27.08%) , Theory of VSEPR (20.83%), Electron Domain Theory (18.75%), Polarity of Molecul (27.08%), Van der Waals Forces (14.58%), and Hydrogen Bond (29.17%). The result of identification of students' misconception is expected to be helpful in handling misconception at student earlier so as not to hamper students in learning. Keywords Misconception, Chemical Bonding, Four-Tier Multiple-Choice Test